Fuzzy Soft Modules Over Fuzzy Soft Rings - Alhusiny, Amjad (Iraqi Journal of Science, 2024)
Letbe anmodule, and letbe a set, letbe a soft set over. Thenis said to be a fuzzy soft module overiff,is a fuzzy submodule of. In this paper, we introduce the concept of fuzzy soft modules over fuzzy soft rings and some of its properties and we define the concepts of quotient module, product and coproduct operations in the category ofmodules.